Ni-doped nanoflower structure Ni-V2O5-coated NC and preparation method and application thereof
By doping Ni in V2O5 to form a nanoflower-like Ni-V2O5@NC catalyst, the problems of low activity, poor conductivity and poor stability caused by the prone to agglomeration of V2O5 catalysts are solved, and electrocatalytic performance with high activity, conductivity and stability are achieved.
Patent Information
- Application Number
- CN202411723627.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-28
AI Technical Summary
The existing V2O5 catalysts have problems such as low catalytic activity, poor conductivity and poor stability due to prone to agglomeration.
The catalyst was prepared by doping Ni into V2O5 to form a nanoflower-like Ni-V2O5@NC, and the catalyst was prepared by hydrothermal reaction and annealing treatment.
The activity, conductivity and stability of the catalyst are improved, and the catalytic activity and electrochemical properties of the redox reaction (OER) are enhanced.
Smart Images

Figure CN119615247A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrolyzing water to produce oxygen, and in particular to a Ni-doped nanoflower structure Ni-V2O5@NC and a preparation method and application thereof. Background Art
[0002] The environmental pollution caused by the increase in fossil fuel consumption has prompted people to conduct in-depth research on clean renewable resources. Water electrolysis is a process that converts electrical energy into chemical energy by decomposing water into hydrogen and oxygen. Water electrolysis includes the oxygen evolution reaction (OER) at the anode and the hydrogen evolution reaction (HER) at the cathode. Among them, OER is the rate-controlling step of the water decomposition reaction, which needs to overcome a high overpotential, involves four electron transfer reaction mechanisms and the generation of intermediate species, resulting in slow kinetics. Therefore, highly active electrocatalysts are needed to improve the efficiency of OER. Among the existing catalysts, RuO2 and IrO2 exhibit high OER catalytic activity, but due to poor stability, high price, rarity and short service life, they cannot meet the needs of practical applications. Therefore, it is still a challenge to develop new electrocatalysts with high activity, strong conductivity and good stability.
[0003] Vanadium-based catalysts have good catalytic performance in the process of water electrolysis. Among them, as a relatively stable phase of vanadium, V2O5 has high activity in a wider pH range. The V element in V2O5 has a variety of oxidation states and abundant V=O. By adjusting the electronic structure of the V element ([Ar]3d 3 4s 2 ), stabilize the oxygen sites in the atomic network, enrich the active intermediates (*OOH), promote the intermediate reaction, and thus reduce the reaction barrier. Specifically, in the OER, the V2O5 obtained by ammonium metavanadate annealing can drive 10mA cm -2 The current density is 44 mV·dec. -1 The V2O5 nanorod structure was obtained by polyvinyl alcohol-assisted solution synthesis technology. The polymer was oxidized to produce voids and coated on nickel foam. -2 The overpotential at a current density of 310 mV was obtained. V2O5 nanorods synthesized by hydrothermal method with ammonium metavanadate and nitric acid also showed good catalytic activity (442 mV@10 mA cm -2 , Tafel slope is 135mV·dec -1 ). Doping active metal elements (such as Ni, Fe, Co, etc.) as promoters can improve the OER catalytic performance of V2O5. Constructing highly dispersed Co(OH)2 grown on V2O5 nanoflowers, it can be found at 10mV·cm -2 It provides a low overpotential of 320 mV at a current density of 1.5 %.
[0004] However, V2O5 has some defects: 1) Easy to agglomerate, resulting in low catalytic activity: Conventionally synthesized V2O5 is easy to agglomerate and form larger particles, resulting in low porosity, small specific surface area and few active sites, thereby reducing catalytic activity. 2) Poor conductivity: V2O5 has a high ionic bond density, and the mobility of electrons in the energy band formed by the d orbital is limited, which reduces the freedom of electrons in the material and exhibits low conductivity. 3) Poor stability: In alkaline OER, V metal will dissolve and over-oxidize, thereby destroying the structure of the catalyst and reducing stability. Therefore, relying solely on V2O5 itself, improving its electrocatalytic efficiency remains a major obstacle. Summary of the invention
[0005] Technical problem to be solved: In view of the problem that V2O5 catalysts in the prior art are easy to agglomerate, resulting in low catalytic activity, poor conductivity and poor stability, the present invention proposes a Ni-doped nanoflower structure Ni-V2O5@NC and a preparation method and application thereof. The Ni-doped V2O5 nanoflower structure is formed by a direct mixing reaction of ammonium metavanadate, oxalic acid and nickel nitrate. The V2O5 nanoflower structure after Ni doping has a high active specific surface area. After Ni doping, the overall conductivity of the material can be effectively improved, and the number of oxygen vacancies in V2O5 can be reduced, so that the prepared Ni-doped nanoflower structure Ni-V2O5 catalyst has higher catalytic activity and conductivity and better stability.
[0006] Technical solution: The first object of the present invention is to provide a method for preparing Ni-doped nanoflower structure Ni-V2O5@NC, the steps are as follows:
[0007] Step 1, adding ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate into water, stirring at room temperature, and obtaining a mixed solution;
[0008] Step 2, subjecting the mixed solution obtained in step 1 to a hydrothermal reaction, washing and drying;
[0009] Step 3: annealing the dried sample in an argon atmosphere to obtain the Ni-doped nanoflower-like structured Ni-V2O5@NC.
[0010] Preferably, in the step 1, the mass ratio of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate is 1:2.1:0.1 to 1:2.1:0.4, and the concentration of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate added to deionized water to form a mixed solution is 0.016 g mL -1 ~0.0175g·mL -1 In this process, the mass of nickel nitrate hexahydrate added needs to be controlled. When a small amount or an excessive amount of nickel nitrate hexahydrate is added, the electrochemical performance and structural stability of the composite are poor.
[0011] Preferably, in the step 1, the mass ratio of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate is 1:2.1:0.3, and the concentration of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate added to deionized water to form a mixed solution is 0.017 g mL -1 .
[0012] Preferably, in step 1, the stirring treatment temperature is 15° C. to 25° C., and the treatment time is 1 h to 2 h.
[0013] Preferably, the temperature of the hydrothermal reaction in step 2 is 150° C. to 200° C., and the treatment time is 18 h to 24 h.
[0014] Preferably, the conditions for annealing in an argon atmosphere in step 3 are as follows: annealing in an argon atmosphere at 500°C ± 50°C for 3h, with a heating rate of 2°C·min -1 .
[0015] The second object of the present invention is to provide a Ni-doped nanoflower structure Ni-V2O5@NC prepared based on the above method.
[0016] The third object of the present invention is to provide an application of the above-mentioned Ni-doped nanoflower structure Ni-V2O5@NC as a catalyst for electrolysis of water to produce oxygen.
[0017] Beneficial effects:
[0018] (1) Ni-doped V2O5 forms a nanoflower structure with a high active specific surface area. The introduction of Ni not only increases the number of active centers on the catalyst surface, but also improves the contact efficiency between the catalyst and the reactants, thereby improving the OER catalytic activity. The Ni-doped nanoflower structure Ni-V2O5@NC catalyst prepared by the present invention has a high specific surface area at 10 mA·cm -2 The overpotential under current density is 292~366mV, among which the catalyst Ni-60-V2O5@NC has a high overpotential under current density of 10mAcm -2 The overpotential at the current density was only 292 mV; the prepared catalyst showed a low Tafel slope (53.2~88.2 mV·dec -1 ), especially the Tafel slope of Ni-60-V2O5@NC catalyst is 53.2 mV·dec -1 , indicating that the Ni-doped nanoflower structure Ni-V2O5@NC prepared in the present invention has good reaction kinetics.
[0019] (2) Ni has a high electrical conductivity. After doping, it can effectively improve the overall electrical conductivity of the material, improve the electron flow path inside the material, reduce resistance, and enable electrons to transfer quickly on the catalyst surface. In addition, the d orbital of Ni will interact with the d orbital of the V atom to form a strong electronic coupling, promote electron delocalization, and thus improve conductivity. The Ni-doped nanoflower structure Ni-V2O5@NC catalyst prepared by the present invention has a charge transfer resistance value of 24.4 to 60Ω, among which the charge transfer resistance value of Ni-60-V2O5@NC is the lowest, only 24.4Ω. The results show that the electron transfer rate of the Ni-60-V2O5@NC catalyst in OER is faster, further indicating that the increase in Ni doping will increase conductivity.
[0020] (3) Ni helps to form a more stable oxidation state. Ni doping reduces the number of oxygen vacancies in V2O5, optimizes the V2O5 lattice structure, and reduces catalyst deactivation caused by structural changes during the catalytic process. The catalyst Ni-60-V2O5@NC prepared by the present invention has a stable oxidation state at 50 mV·s -1 The stability of the cycle was tested for 1000 times at a constant scan rate of . Compared with the initial curve, the current density after cycling was 10 mA cm -2 The overpotential increased by only 5 mV, indicating its good catalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the scanning electron microscope (SEM) image of Ni-V2O5@NC synthesized in Example 1.
[0022] Figure 2 This is the transmission electron microscope (TEM) image of Ni-V2O5@NC synthesized in Example 1.
[0023] Figure 3 This is the high magnification transmission electron microscopy (HRTEM) image of Ni-V2O5@NC synthesized in Example 1.
[0024] Figure 4 This is the mapping diagram of Ni-V2O5@NC synthesized in Example 1. Figure (j) is the photoelectron diffraction diagram of Ni-60-V2O5@NC, where C, N, O, V and Ni are the EDS mapping diagrams of the corresponding elements.
[0025] Figure 5 This is the energy dispersive spectroscopy (EDS) diagram of Ni-V2O5@NC synthesized in Example 1.
[0026] Figure 6 The Raman spectra of Ni-V2O5@NC synthesized in Examples 1, 2, 3, and 4 are shown.
[0027] Figure 7X-ray diffraction (XRD) patterns of Ni-V2O5@NC synthesized in Examples 1, 2, 3, and 4.
[0028] Figure 8 Electron paramagnetic (EPR) patterns of Ni-V2O5@NC synthesized in Examples 1, 2, 3, and 4.
[0029] Fig. 9 This is the X-ray photoelectron spectroscopy (XPS) diagram of Ni-V2O5@NC prepared in Example 1.
[0030] Fig.10 This is the thermogravimetric analysis (TGA) diagram of Ni-V2O5@NC prepared in Example 1.
[0031] Fig.11 Fourier transform infrared (FT-IR) spectra of Ni-V2O5@NC prepared in Examples 1, 2, 3, and 4.
[0032] Fig.12 Linear sweep voltammetry (LSV) curves of oxygen evolution reaction of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4.
[0033] Fig.13 The Tafel slope diagram of the oxygen evolution reaction of the Ni-V2O5@NC catalyst prepared in Examples 1, 2, 3, and 4.
[0034] Fig.14 Electrochemical impedance spectroscopy (EIS) graphs of oxygen evolution reaction of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4.
[0035] Fig.15 The electrochemical active surface area (ECSA) diagram of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4.
[0036] Fig.16 This is the cyclic stability diagram of the Ni-60-V2O5@NC catalyst prepared in Example 1. DETAILED DESCRIPTION
[0037] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is described in detail below with reference to the accompanying drawings and embodiments.
[0038] In view of the problems existing in V2O5, in the present invention, we designed and prepared Ni-doped V2O5 nanoflowers. Taking advantage of the excellent conductivity and activity of the transition metal element Ni, Ni was doped into the V2O5 nanoflowers, which were also doped with nitrogen and carbon to form Ni-V2O5@NC, a stable nanoflower. This material has the following advantages: 1) High activity: Ni elements are uniformly doped into V2O5, and the formed nanoflower structure has a larger active specific surface area, providing more active sites for OER, thereby increasing the reaction activity. 2) High conductivity: Ni has a high conductivity, and after doping, it can effectively improve the overall conductivity of the material, change the chemical environment around the atoms inside the original catalyst material crystal, optimize the electron flow path inside the material, and make the electrons quickly transfer on the catalyst surface. In addition, Ni interacts with the d orbital of the V atom, promoting electron delocalization, thereby improving conductivity. 3) Good stability: The structural stability of V2O5 is poor. Under Ni doping, the crystal structure is optimized, thereby improving the OER stability of the catalyst.
[0039] The drugs used in the present invention were purchased from Aladdin Reagent Co., Ltd. and used without further purification.
[0040] The preparation method of Ni-doped V2O5 nanoflowers of the present invention comprises the following specific steps:
[0041] 1) 0.2 g of ammonium metavanadate, 0.42 g of oxalic acid dihydrate and 0.02 g to 0.08 g of nickel nitrate hexahydrate were added to 40 mL of deionized water and stirred at 15°C to 25°C for 1 h to 2 h. The mass ratio of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate was 1:2.1:0.1 to 1:2.1:0.4. The concentration of the mixed solution formed by adding ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate into deionized water was 0.016 g·mL -1 ~0.0175g·mL -1 ;
[0042] 2) hydrothermally treating the prepared ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate solution at 150° C. to 200° C. for 18 h to 24 h, centrifugally separating and drying;
[0043] 3) The obtained solid was annealed at 500℃±50℃ for 3h in an argon atmosphere to obtain Ni-doped V2O5 nanoflower structure Ni-V2O5@NC, wherein the heating rate was 2℃·min -1 .
[0044] The specific embodiments are as follows:
[0045] Example 1
[0046] This embodiment provides a method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC, the steps of which are as follows:
[0047] 1) Weigh 0.2 g of ammonium metavanadate, 0.42 g of oxalic acid dihydrate and 0.06 g of nickel nitrate hexahydrate, add them into 40 mL of deionized water, and stir at room temperature for 1 h to form a mixed solution;
[0048] 2) The obtained solution was transferred to a 100 mL autoclave and subjected to constant temperature hydrothermal treatment at 200°C for 24 h. After cooling to room temperature, the sample was obtained by centrifugation, washing and drying;
[0049] 3) The dried sample was annealed in argon at 500 °C for 3 h to obtain Ni-doped V2O5 nanoflower structure Ni-60-V2O5@NC, where the heating rate was 2 °C min -1 .
[0050] Figure 1 This is a SEM image of the Ni-V2O5@NC catalyst synthesized in this example. From the image, we can observe that the Ni-V2O5@NC nanoflowers are formed by a relatively uniformly distributed sheet structure after Ni doping.
[0051] Figure 2 This is the TEM image of Ni-V2O5@NC synthesized in this example. From the image, we can observe the nanoflower structure of Ni-V2O5@NC, and no agglomeration occurs.
[0052] Figure 3 This is the HRTEM image of the Ni-V2O5@NC catalyst synthesized in this example. From the image, it can be observed that the interplanar spacing of Ni-V2O5@NC is 0.35nm (110).
[0053] Figure 4 This is the Ni-V2O5@NC Mapping diagram for this example. Figure 4 It can be seen that C, N, O, V and Ni elements are distributed on the surface of the material, and the distribution is the same, indicating uniform doping of Ni, N and C.
[0054] Figure 5 This is the EDS spectrum of Ni-V2O5@NC synthesized in this example. Figure 5 It can be seen that it contains Cu, C, N, O, V and Ni elements, among which the Cu element comes from the copper mesh, that is, the material contains C, N, O, V and Ni elements, and their mass contents are 8.56%, 0.01%, 14.04%, 74.96% and 2.43% respectively.
[0055] Fig. 9 This is the XPS elemental electron spectrum of the Ni-V2O5@NC catalyst prepared in Example 1. Fig. 9It can be seen that the prepared material is mainly composed of C, N, O, V and Ni elements.
[0056] Fig.10 This is the TGA graph of the Ni-V2O5@NC catalyst synthesized in Example 1. From the graph, it can be observed that Ni-V2O5@NC has a small loss during the heating process from room temperature to 900°C, indicating that the C content is 8.01%.
[0057] Example 2
[0058] The same as Example 1, except that the amount of nickel nitrate hexahydrate added in this example is 0.02 g, specifically as follows:
[0059] 1) Weigh 0.2 g of ammonium metavanadate, 0.42 g of oxalic acid dihydrate and 0.02 g of nickel nitrate hexahydrate, add them into 40 mL of deionized water, and stir at room temperature for 1 h to form a mixed solution;
[0060] 2) Same as step 2) of Example 1;
[0061] 3) The same as step 3 of Example 1). Finally, the Ni-doped V2O5 nanoflower structure Ni-20-V2O5@NC was obtained.
[0062] The Raman, XRD, EPR and FT-IR images of the product obtained in this example are shown in Figure 6 , 7 , 8, 11. The positions of the Raman peak and FT-IR peak of Ni-20-V2O5@NC are the same, and the intensity is lower than that of Ni-60-V2O5@NC. The XRD peak intensity is also lower than that of Ni-60-V2O5@NC, which is attributed to the fact that Ni doping improves the crystallinity of V2O5. The oxygen vacancy content is higher than that of Ni-60-V2O5@NC, indicating that Ni doping optimizes the crystal structure.
[0063] Example 3
[0064] The same as Example 1, except that the amount of nickel nitrate hexahydrate added in this example is 0.04 g, specifically as follows:
[0065] 1) Weigh 0.2 g of ammonium metavanadate, 0.42 g of oxalic acid dihydrate and 0.04 g of nickel nitrate hexahydrate, add them into 40 mL of deionized water, and stir at room temperature for 1 h to form a mixed solution;
[0066] 2) Same as step 2) of Example 1;
[0067] 3) The same as step 3 of Example 1). Finally, the Ni-doped V2O5 nanoflower structure Ni-40-V2O5@NC was obtained.
[0068] The Raman, XRD, EPR and FT-IR images of the product obtained in this example are shown in Figure 6 , 7 , 8, 11.
[0069] Example 4
[0070] The same as Example 1, except that the amount of nickel nitrate hexahydrate added in this example is 0.08 g, specifically as follows:
[0071] 1) Weigh 0.2 g of ammonium metavanadate, 0.42 g of oxalic acid dihydrate and 0.08 g of nickel nitrate hexahydrate, add them into 40 mL of deionized water, and stir at room temperature for 1 h to form a mixed solution;
[0072] 2) Same as step 2) of Example 1;
[0073] 3) The same as step 3 of Example 1). Finally, Ni-doped V2O5 nanoflower structure Ni-80-V2O5@NC was obtained.
[0074] The Raman, XRD, EPR and FT-IR images of the product obtained in this example are shown in Figure 6 , 7 , 8, 11. The positions of the Raman peak and FT-IR peak of Ni-80-V2O5@NC are the same, and the intensity is lower than that of Ni-60-V2O5@NC. The XRD peak intensity is also lower than that of Ni-60-V2O5@NC, which is attributed to the increase in the disorder of the V2O5 crystal structure due to excessive Ni doping. In addition, the oxygen vacancy content is higher than that of Ni-60-V2O5@NC. Excessive Ni doping will promote the formation of oxygen vacancies and produce lattice defects.
[0075] Figure 6 The Raman graphs of Ni-V2O5@NC synthesized in Examples 1 to 4 are shown in Table 1. Figure 6 It can be seen that V=O, VO, OVO and OV=O groups exist in the prepared Ni-V2O5@NC.
[0076] Figure 7 The XRD patterns of Ni-V2O5@NC synthesized in Examples 1 to 4 are shown in Figure 2. Figure 7 It can be seen that the product prepared in Example 1 contains several characteristic peaks, namely (001), (110), (002), (003) and (312), which correspond to the standard diffraction peaks of VO2 (PDF#31-1438). This is because the introduction of Ni reduces the valence state of V.
[0077] Figure 8 The EPR diagram of Ni-V2O5@NC synthesized in Examples 1 to 4. Figure 8It can be seen that Ni doping leads to a significant reduction in the number of oxygen vacancies. The oxygen vacancies in Ni-V2O5@NC decrease with the increase of Ni content, proving that the incorporation of Ni optimizes the defect structure of V2O5. Ni-60-V2O5@NC has the least oxygen vacancies, and its EPR curve is a slanted line. The addition of Ni causes the oxygen vacancies to be a slanted line, which is due to the shift in spectral absorption caused by Ni atom doping.
[0078] Fig.11 FT-IR images of Ni-V2O5@NC prepared in Examples 1 to 4. Fig.11 It can be seen that the prepared Ni-V2O5@NC has relatively rich functional groups (OH, C=O, CO, V=O, VO and VOV).
[0079] Application Examples
[0080] The catalysts prepared in Examples 1 to 4 were used for parallel tests:
[0081] OER: 5 mg of catalyst was evenly dispersed in a mixed solution of 950 μL of anhydrous ethanol and 50 μL of Nafion solution (5 wt%), and then 5 μL of catalyst ink was dropped on the surface of the glassy carbon electrode. Before the electrochemical experiment, the electrolyte was purified with pure nitrogen for 30 minutes. Then, the newly prepared working electrode was immersed in the electrolyte. The electrochemical performance test was completed in a typical three-electrode system at room temperature (about 25 ° C). With a glassy carbon electrode (GCE, diameter: 3 mm, area: 0.07 cm 2 ) as the working electrode, graphite rod as the counter electrode and Hg / HgO as the reference electrode to test the electrochemical performance of oxygen evolution reaction. All reported potentials were converted to reversible hydrogen electrode (RHE) using the following formula: E (RHE) =E (Hg / HgO) +0.0591*pH+0.098V. All electrochemical tests were performed on a CHI660E electrochemical workstation (Shanghai). The polarization curves were obtained by LSV scanning in the voltage range of 0 to 0.8 V at room temperature with a scanning rate of 5 mV s -1 The overpotential value is defined by the Tafel equation: η=a+blog|j|, where η (V) is the overpotential, j(mAcm -2 ) is the current density, B (mV dec -1 ) represents the Tafel slope.
[0082] Through the double layer capacitance (C dl , in mF) to evaluate the electrochemical surface area (ECSA): ECSA = C dl / C sCyclic voltammetry (CV) was performed at 20 mV s at −0.1 V to 0.1 V in 1 mol / L KOH. -1 , 40mV s -1 , 60mV s -1 , 80mV s -1 and 100mV s -1 ECSA was determined by fitting the slope Δj = (ja-jc) / 2 at 0 V vs. RHE and different scan rates. dl Assuming the specific capacitance of the flat surface is 40 μF cm -2 (C s ). ECSA is achieved by normalizing the double layer capacitance to the standard specific capacitance.
[0083] EIS was recorded in the frequency range of 1000kHz to 10mHz, with 10 points tested in every 10-fold frequency range. The amplitude of the sinusoidal potential signal was 5mV. The measurements were performed at 50mV s -1 The stability of the catalyst was tested for 1000 cycles at a constant scan rate of . The polarization curves were compared with the initial curves to evaluate the catalyst stability after 1000 cycles.
[0084] Fig.12 The LSV curves of the oxygen evolution reaction of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4 are shown in FIG. Fig.12 It can be seen that compared with Ni-20-V2O5@NC (366mV@10mA·cm -2 ), Ni-40-V2O5@NC(343mV@10mA·cm -2 ) and Ni-80-V2O5@NC (357mV@10mA·cm -2 ), the Ni-60-V2O5@NC prepared in Example 1 only needs 292 mV to reach 10 mA·cm -2 Current density.
[0085] Fig.13 The Tafel slope diagram of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4. Fig.13 It can be seen that compared with Ni-20-V2O5@NC (74.5mV·dec -1 )、Ni-40-V2O5@NC(88.2mV·dec -1 )、Ni-80-V2O5@NC(77.7mV·dec -1 ) compared with the Ni-60-V2O5@NC (53.2 mV·dec -1 ) has a smaller Tafel slope, indicating that its catalyst has high OER activity.
[0086] Fig.14 The EIS graphs of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4 are shown in Figure 1. Fig.14 It can be seen that compared with Ni-20-V2O5@NC (57.7Ω), Ni-40-V2O5@NC (60.0Ω), and Ni-80-V2O5@NC (44.4Ω), Ni-60-V2O5@NC (24.4Ω) has a lower charge transfer resistance, indicating that the Ni-60-V2O5@NC catalyst has high conductivity.
[0087] Fig.15 The ECSA diagrams of Ni-V2O5@NC catalysts prepared in Examples 1, 2, 3, and 4 are shown in Figure 2. Fig.15 Visible: Compared with Ni-20-V2O5@NC(2.31cm -2 )、Ni-40-V2O5@NC(2.57cm -2 ) and Ni-80-V2O5@NC(2.54cm -2 ) compared to Ni-60-V2O5@NC (2.66cm -2 ) has a larger electrochemically active specific surface area, indicating that Ni-60-V2O5@NC has better catalytic activity.
[0088] Fig.16 The cyclic stability diagram of the Ni-V2O5@NC catalyst prepared in Example 1. Fig.16 It can be seen that compared with the initial curve, the current density after cycling is 10 mA cm -2 The overpotential increased by only 5 mV, indicating its good catalytic stability.
[0089] In summary, we have successfully synthesized a new type of catalyst Ni-V2O5@NC with high stability and high activity of Ni-doped V2O5 nanoflowers, and exhibited good electrochemical performance in OER. Specifically, Ni-doped V2O5 forms a nanoflower-like Ni-V2O5@NC with a stable crystal structure. This material has the following advantages: 1) High reactivity: Ni-doped V2O5 forms a nanoflower-like structure, which increases the number of surface active centers and reduces the adsorption energy of the reaction transition state at the active center, thereby increasing the catalytic reaction activity of OER. In addition, Ni, as a good catalyst material, provides additional reactive sites for OER. 2) High conductivity: The interaction between the doped Ni and the d orbital of the V atom promotes the delocalization of electrons, improves the electron flow path in the material, reduces the charge transfer resistance, and enables electrons to be quickly transferred on the catalyst surface, thereby improving the conductivity. 3) Strong stability: Ni doping inhibits the stacking and agglomeration of the V2O5 sheet structure, maintains the activity and structural integrity of the catalyst, and improves the stability of the catalyst. Based on the above advantages, Ni-V2O5@NC exhibits good electrochemical performance in OER (low overpotential: 292 mV@10 mA cm -2 ).
[0090] Finally, it should be noted that the above implementation modes are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned implementation modes, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned implementation modes can still be modified, or some or all of the technical features therein can be replaced by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the implementation modes of the present invention.
Claims
1. A method for preparing Ni-doped nanoflower structure Ni-V2O5@NC, characterized in that: Here are the steps: Step 1, adding ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate into water, stirring at room temperature, and obtaining a mixed solution; Step 2, subjecting the mixed solution obtained in step 1 to a hydrothermal reaction, washing and drying; Step 3: annealing the dried sample in an argon atmosphere to obtain the Ni-doped nanoflower-like structured Ni-V2O5@NC.
2. The method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC according to claim 1, characterized in that: In the step 1, the mass ratio of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate is 1:2.1:0.1 to 1:2.1:0.4, and the concentration of the mixed solution formed by adding ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate into deionized water is 0.016 g·mL -1 ~0.0175g·mL -1 .
3. The method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC according to claim 1, characterized in that: In the step 1, the mass ratio of ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate is 1:2.1:0.3, and the concentration of the mixed solution formed by adding ammonium metavanadate, oxalic acid dihydrate and nickel nitrate hexahydrate into deionized water is 0.017 g·mL -1 .
4. The method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC according to claim 1, characterized in that: In the step 1, the stirring treatment temperature is 15° C. to 25° C., and the treatment time is 1 h to 2 h.
5. The method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step 2 is 150° C. to 200° C., and the treatment time is 18 h to 24 h.
6. The method for preparing a Ni-doped nanoflower structure Ni-V2O5@NC according to claim 1, characterized in that: The conditions for annealing in an argon atmosphere in step 3 are as follows: annealing in an argon atmosphere at 500°C ± 50°C for 3 hours, with a heating rate of 2°C·min -1 .
7. A Ni-doped nanoflower structure Ni-V2O5@NC prepared by the method according to any one of claims 1 to 6.
8. Use of a Ni-doped nanoflower structure Ni-V2O5@NC as a catalyst in electrolysis of water to produce oxygen based on claim 7.
Citation Information
Patent Citations
Preparation method for vanadium trioxide doped powder material
CN102674457A
Preparation method of V2O3@Ni bifunctional composite electrocatalyst
CN110560078A